Host sex and age typically explain variation in parasitism of rock ptarmigan: implications for identifying determinants of exposure and susceptibility. (26th October 2020) - Nielsen, Ó. K.; Morrill, A.; Skírnisson, K.; Stenkewitz, U.; Pálsdóttir, G. R.; Forbes, M. R.
Abstract : Measures of parasitism often differ between hosts. This variation is thought due in part to age or sex differences in exposure to parasites and/or susceptibility to parasitism. We assessed how often age or sex biases in parasitism were found using a large, multi‐year (2006–2017) dataset of 12 parasite species of Icelandic rock ptarmigan ( Lagopus muta ). We found host traits (i.e. age and/or sex) accounted for significant variation in abundance of 11 of the 12 parasite species. We often found increased abundance among juvenile hosts, although significant adult biases were observed for three parasite species. Additionally, higher levels of parasitism by many species were observed for female hosts, contrary to frequent male biases in parasitism reported for other vertebrates. Abundance of six parasite species was best explained by interactions between host age and sex; some degree of decrease in abundance with host age was present for both male and female hosts for four of those parasite species. We consider various host and parasite traits that could account for observed singular and repeated patterns of age and/or sex biases in parasitism (e.g. age‐ and sex‐related grouping behaviours, age‐specific mortality in relation to parasitism, acquisition of greater immunity with age). This work provides a foundation for future studies investigating age‐related differences in acquired immunity and age‐specific parasite‐mediated mortality for males and females, as well as studies on interactions between co‐infecting parasite species.